PINTAR MATEMATIKA CERDAS DIGITAL : PENGENALAN CODING UNTUK MENINGKATKAN KEMAMPUAN KOMPUTASIONAL ANAK DI SD BAWANG TIKAR - Annisa Nur Azizah; Fitria Apriani; Fajar Fadillah Wibowo; Umu Ulfa (Jurnal Abdi Insani, 2025)
Coding is a 21st-century skill that develops students’ computational, logical, and creative thinking abilities. However, at the elementary school level, coding-based learning is rarely implemented due to limited digital facilities and teachers’ lack of experience in integrating such activities into classroom practice. Through the Community Service Program (PKM) titled “Smart Digital Math: Introducing Coding to Enhance Computational Thinking Skills of Elementary Students at SD Bawang Tikar”, the implementing team introduced basic coding concepts without using digital devices. This program aimed to improve students’ logical thinking skills and interest in learning mathematics through engaging and interactive activities. The implementation method consisted of four stages: planning, implementation, mentoring, and evaluation. The learning media included Student Worksheets (LKPD) and logic-based educational games designed according to the characteristics of elementary students. The results showed that students became more enthusiastic, active, and motivated during the learning process. Teachers also gained new insights into developing creative and contextual teaching methods that can be applied without relying on digital technology. This program successfully fostered early computational thinking skills and enriched mathematics learning with a more enjoyable experience.